2012
DOI: 10.1097/fjc.0b013e31823cc58b
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Single or Combined Administration of Cocaine and Testosterone on Cardiovascular Function and Baroreflex Activity in Unanesthetized Rats

Abstract: Abuse of cocaine and androgenic-anabolic steroids has become a serious public health problem. Despite reports of an increase in the incidence of simultaneous illicit use of these substances, potential toxic interactions between cocaine and androgenic-anabolic steroids in the cardiovascular system are unknown. In the present study, we investigated the effect of single or combined administration of testosterone and cocaine for 1 or 10 consecutive days on basal cardiovascular parameters, baroreflex activity, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
4
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(44 citation statements)
references
References 59 publications
6
32
4
2
Order By: Relevance
“…The direct recording of BP and HR was conducted using the implanted arterial cannula in the femoral artery in accordance with previous work ( [23,50,51,10]). The recording was done while the animals were awake and freely moving.…”
Section: Femoral Artery Catheterizationmentioning
confidence: 99%
“…The direct recording of BP and HR was conducted using the implanted arterial cannula in the femoral artery in accordance with previous work ( [23,50,51,10]). The recording was done while the animals were awake and freely moving.…”
Section: Femoral Artery Catheterizationmentioning
confidence: 99%
“…Cocaine’s acute effects on cardiovascular function are well described and include hypertension, coronary vasoconstriction and cardiac arrhythmias [10], [13]. Cardiovascular toxicity following chronic cocaine exposure is less understood, but clinical and preclinical studies have reported myocarditis, arrhythmias, alterations in baroreflex activity, and vascular dysfunctions [10], [14]. Studies in humans and animals have also associated chronic AAS administration with cardiovascular complications, including hypertension, atherosclerosis, cardiac pathologies, impairment of baroreflex activity and changes in vascular function [12], [14][16].…”
Section: Introductionmentioning
confidence: 99%
“…Cardiovascular toxicity following chronic cocaine exposure is less understood, but clinical and preclinical studies have reported myocarditis, arrhythmias, alterations in baroreflex activity, and vascular dysfunctions [10], [14]. Studies in humans and animals have also associated chronic AAS administration with cardiovascular complications, including hypertension, atherosclerosis, cardiac pathologies, impairment of baroreflex activity and changes in vascular function [12], [14][16]. Interestingly, preclinical studies have demonstrated that concomitant AAS and cocaine treatment potentiate the cardiovascular effects of each other [17][19].…”
Section: Introductionmentioning
confidence: 99%
“…Segundo Engi et al,(2012) o prejuízo da atividade do barorreflexo pode contribuir para a patogênese de várias doenças cardiovasculares. Nesse contexto, a reversão eficiente de mudanças autonômicas provocadas pelo estresse é importante para reduzir as chances de patologias que em longo prazo podem induzir alterações cardiovasculares (Crestani et al, 2010c).…”
Section: Sumáriounclassified
“…Vários estudos na literatura demonstram que uma das formas de avaliar a sensibilidade barorreflexa é através da quantificação da resposta reflexa de FC frente às variações de PA desencadeadas por drogas vasoativas (Crestani et al, 2006, Resstel et al, 2006b, Crestani et al, 2010a, Engi et al, 2012. No entanto, neste estudo a sensibilidade do barorreflexo também foi avaliada no domínio do tempo por meio do método da sequência.…”
Section: Figura 38 (Ab)unclassified